Using Four Types of Narrative in Teaching Writing for University Students in Indonesia - Yuskar, Bobby (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2021)
This paper is written in a form of library research and its purpose is to search ideas in giving description of how English lecturer able to develop students’ writing skill using narrative writing. The writer selects four types of narrative to improve students’ writing skill after reading several theories from scholars and analyzing their ideas on the application of four narratives. By applying four types of narrative, university students in Indonesia will have better understanding in writing good narrative compositions. And they will also learn how to express their ideas and write them smoothly in the form of narrative writing. Furthermore, the variety of passages in these narrative writings can motivate students to create interesting writing since the nature of these narratives are reflecting their experience directly. In this library research, the writer finds out several advantages which can be obtained from these four narratives. The advantages students can get such as, learn to arrange chronological order inside their writing, expressing experience in dramatic ways, showing the dynamic interpersonal relationships, and increasing their possession for new vocabularies relatively help students to make good narrative writing.